Nephron sparing surgery for a patient with a complicated solitary functioning kidney and a giant pT3 renal cell carcinoma: A case report - Yu, Minghao; Zhou, Jiatong; Shangguan, Xun; Qian, Subo; Ding, Jie; Qi, Jun (Frontiers in Surgery, 2023)
A solitary functioning kidney (SFK) with renal cell carcinoma (RCC) is an imperative indication for nephron-sparing surgery (NSS). Nevertheless, a giant pT3 RCC mass (maximum diameter >20 cm) on the functioning side of a patient with SFK is extremely rare. However, whether NSS is more beneficial than radical nephrectomy (RN) in such patients is controversial. Here, we present the case of a 71-year-old female patient with a 20 cm*16 cm RCC mass in the SFK, who initially presented with hematuria and acute urinary tract obstructive anuria caused by renal calculi. The patient underwent NSS treatment after our evaluation, and the 26-month follow-up revealed that her renal function recovered to the state before the tumor formation. In addition, no relapse or metastasis was detected.